Prospects of the construction of dam in semiarid brazilian and its implications in the region Seridó of the state of Rio Grande do Norte - Pereira Neto, Manoel Cirício (Sociedade & Natureza, 2017)
The construction of the water reservoirs in the Brazilian semiarid becoming one of the first engineeringsystems to “combat” or mitigate the effects produced by the drought phenomenon. The objective of thiswork is to analyze the perspectives that guide the policy of construction of dams over the years in theBrazilian semiarid, emphasizing the different implications for the region of Seridó Potiguar, consideredone of the most densely damed of the country. It is observed that the the construction of dam in the Bra-zilian semiarid, and in particular the Seridó region, although initially designed mainly for human watersupply and animal, inherent to the drought relief discourse, currently plays importants role of coexistencewith this phenomenon, linked to other numerous economic, cultural and environmental activities of theregional scenario. There are several roles and outlooks related to the environmental context, the discoursesand intentions of the different social, economic and statutory agents based on the conjecture, demandsand complexities over time. Thus, it is important to insert, in parallel, to the debate on the policies andmanagement of water resources in the Brazilian semi-arid region, and in particular on the Seridó region,the question of the multiple purposes related to the use and land subdivision of the area influence